An Audit to Evaluate the Etiologies and Preventability of Hyperkalemia in Inpatients: Focus on Modifiable Risk Factors and Medication-Related Triggers - Shah, Syed Hussaini; Ahmad, Zubair; Safi Ullah; Nawaz, Sajid; Aurangzeb, Laraib; Farooq, Moazzam; Sohail, Aamir; Ahmad, Jamil; Safdar, Sundas; Hanfi, Hanifullah; Ullah, Naqeeb (Indus Journal of Bioscience Research, 2025)
Background: Hyperkalemia, defined as a serum potassium level >5.0 mmol/L, is a frequent yet underrecognized clinical emergency in hospitalized patients. It is associated with substantial morbidity and mortality, particularly among individuals with chronic kidney disease (CKD), diabetes mellitus, and cardiovascular diseases. Medication-related factors such as use of renin-angiotensin-aldosterone system inhibitors and NSAIDs contribute significantly to its occurrence. Objective: This audit aimed to evaluate the etiologies and preventability of hyperkalemia in inpatients, with a focus on modifiable clinical risk factors and drug-related triggers. Methods: A retrospective audit was conducted at Lady Reading Hospital, Peshawar, over a six-month period. Adult inpatients with serum potassium levels >5.5 mmol/L were included, excluding those on dialysis or with familial potassium disorders. Data on demographics, comorbidities, medications, laboratory findings, and outcomes were extracted and analyzed. Preventability was assessed using Institute for Safe Medication Practices (ISMP) criteria. Results: Among 152 patients (mean age: 61.4 ± 13.2 years), 60.5% were male. CKD (49.3%), hypertension (62.5%), and diabetes (38.2%) were common comorbidities. Medication-related triggers were identified in 69.1% of cases, particularly ACE inhibitors (34.9%) and potassium-sparing diuretics (26.3%). A total of 45.4% of hyperkalemic episodes were deemed preventable, with inadequate monitoring (68.1%) and inappropriate drug use in renal impairment (49.3%) as leading causes. Mortality occurred in 5.9% of patients. Conclusion: Nearly half of hyperkalemia episodes in this tertiary care setting were preventable. Enhanced surveillance, appropriate drug adjustments, and regular electrolyte monitoring can significantly mitigate this risk and improve patient outcomes.